Administration of IL-18BP by gene therapy reduces inflammation and prevents joint destruction by downregulation of MMP9 in rat AIA: role of MMP9 in bone and joint destruction in arthritis. (22nd February 2011) - Marotte, Hubert; Ahmed, Salahuddin; Amin, M Asif; Ruth, Jeffrey H; Campbell, Phillip L; Rabquer, Bradley J; Lesch, Charles; Lewis, Benjamin P; Dudler, Jean; Koch, Alisa E
Abstract : Background and objectives: Interleukin 18 (IL-18) is a pleiotropic cytokine involved in rheumatoid arthritis (RA) pathogenesis. This study was carried out to evaluate the efficacy of IL-18 binding protein (IL-18BP) gene therapy in the rat adjuvant-induced arthritis (AIA) model and to decipher the mechanisms by which IL-18BP delivery lessens bone destruction. Materials and methods: Arthritis was induced in female Lewis rat by Mycobacterium butyricum and the mRNA expression of IL-18 and IL-18BP was determined in the joints. In a preventive study, rats were divided into an adenovirus producing IL-18BP-Fc (AdmIL-18BP-Fc) group (n=8) and an adenovirus producing green fluorescent protein (AdGFP) group (n=7). On day 8 after AIA induction, adenoviruses were injected. Clinical parameters were assessed. At day 18, during maximal arthritis, the rats were euthanized, ankles were collected and x-rays were performed. mRNA and protein were extracted from joints for analysis by quantitative reverse transcriptase-PCR, multiplex, Western blot and zymography. Results: The authors observed a decrease in the (IL-18BP/IL-18) ratio from day 7 to 45. Administration of AdmIL-18BPd-Fc decreased clinical parameters and prevented bone and joint destruction compared to AdGFP administration. IL-18BP delivery reduced the (receptor activator of nuclear factor κB ligand (RANKL)/osteoprotegerin (OPG)) ratio by 70%, the matrix metalloproteinase 9 (MMP9) level by 33% and the tartrate-resistant acid phosphatase (TRAP) level by 44% in the joint homogenates from AdmIL-18BPd-Fc compared to AdGFP treated rats. Conclusions: In rat AIA, a decrease in the (IL-18BP/IL-18) ratio was observed. IL-18BP delivery prevented joint and bone destruction by downregulating MMP9, (RANKL/OPG) and TRAP, suggesting a potential benefit of a similar therapy in RA. Abstract topics: Towards novel therapeutic strategies.